Gliadin effect on the oxidative balance and DNA damage: An in-vitro, ex-vivo study. Issue 1 (January 2019) - Monguzzi, Erika; Marabini, Laura; Elli, Luca; Vaira, Valentina; Ferrero, Stefano; Ferretti, Francesca; Branchi, Federica; Gaudioso, Gabriella; Scricciolo, Alice; Lombardo, Vincenza; Doneda, Luisa; Roncoroni, Leda
Abstract: Background: Gliadins are involved in gluten-related disorders and are responsible for the alteration of the cellular redox balance. It is not clear if the gliadin-related oxidative stress can induce DNA damage in enterocytes. Aim: To investigate any possible genotoxicity caused by gliadin and to assess its relationship with oxidative stress in vitro and ex vivo . Methods: Caco-2 cells were exposed for 6–12–24 h to increasing concentrations (250 μg/mL–1000 μg/mL) of digested gliadin. We investigated: cytotoxicity, oxidative balance (reactive oxygen species, ROS), DNA damage (comet assay and γ-H2AX detection), transglutaminase type 2 (TG2) activity and annexin V expression. H2AX and 8-OHG immunohistochemistry has been evaluated on duodenal biopsies of celiac subjects and controls. Results: Gliadin induced a significant increase (+50%) of ROS after 12 h of exposition starting with a 500 μg/mL dose of gliadin. Comet assay and γ-H2AX demonstrated DNA damage, evident at the gliadin concentration of 500 μg/mL after 24 h. TG2 activity increased in chromatin and cytoskeleton cellular compartments at different gliadin doses (250/500/1000 μg/mL). The γ-H2AX and 8-OHG immunohistochemistry was altered in the duodenal biopsies of celiac patients. Conclusions: Gliadin induces cellular oxidative stress, DNA damage and pro-apoptotic stimulation in Caco-2 cells and in the duodenal mucosa of celiac patients.